Web based automated e-invoicing system - Lee, Elisabeth Mei Jin (2025)
This project focuses on the development of an e‑Invoice system designed to modernize and automate invoice generation, submission, and verification in compliance with regulatory standards. The purpose of this project is to address the challenges in manual invoicing, including manual errors, lack of transparency in manual invoicing, and the increasing number of fraud risks that had been a pervasive problem within the domain of financial technology and digital tax compliance. The existing problems motivating this project stems from the need for a secure, auditable, and standardized process for generating and submitting invoices, which in turn, ensures data integrity and legal compliance. To address this, a modular approach was adopted which involves mapping invoice data to the UBL 2.1 JSON standard, performing canonicalization for deterministic representation, and cryptographically signing it before submission. Besides, the system integrates with LHDN tax authority APIs for asynchronous validation, generates QR codes for verification, supports cancellation of invoices, notifications, and maintains a ledger for reporting and reconciliation. The preliminary results demonstrate that the platform reliably produces compliant e-invoices, which also accurately detect data mismatches, and enables taxpayers to track invoice status in real time, while QR code verification enhances transparency for end users. The significance of this research lies in its ability to streamline the invoicing process, reduce human error, and provide an auditable digital record, contributing to greater efficiency and regulatory compliance. Therefore, this project has demonstrated a scalable framework, which includes document signing, submission automation, and real-time verification in financial technology applications.